(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
The importance earned by the functional analysis of verbal behavior in behavioral analytic therapy is recent. That’s represents a paradox once the therapy works almost exclusively through verbal interaction between the therapist and the client. Many concepts proposed by Skinner to the analysis of verbal behavior can help in understanding the dysfunctional aspects of verbal behaviors and their influence on client’s non-verbal behaviors. Among them, this paper deal with auditory, non-punitive auditory, distorted tacts, disguised mands, intraverbal behavior, rules control, verbal lapses, metaphorical tacts, meaning by use, and training in tact client’s behavior and their control variables. The categorization of client’s behavior in agreement with such concepts supplies relevant indications concerning their controlling variables, allowing a performance of the therapist in the re-establishment of the client’s behavioral repertoires and the improvement of the dysfunctional verbal repertoires.